The Analysis of Influencer Marketing Factor Towards Consumer Buying Interest (Case Study of Bambam.kuy Beverages in 2023) - Elektania, Digita; Ganjar Mohamad Disastra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to obtain data and information that provides an overview of the influence of influencer marketing on customer buying interest at Bambam.kuy. This study used a quantitative research design with non-probability sampling techniques and purposive sampling. This research involved 100 respondents, all of whom are Bambam.kuy subscribers. Data were analyzed using simple linear regression and tested with SPSS version 28. The results showed that influencer marketing had a positive and significant effect on consumer buying interest as indicated by the results of t count (4.561) > t table value (1.66055) and the level of significance 0.000 < 0.05).